A multimedia item authoring framework for computer-based education - Cheng, I.; Badalov, A. (2009 IEEE International Conference on Multimedia and Expo, 2009)
Perceptually inspired curriculum using multimedia content connects students to subject matter and deepens their understanding of abstract concepts. This approach has become increasingly attractive in education. Multimedia content can arouse user engagement through interactivity and immersion, and thus inspire a student to learn. Differing from multiple-choice, multimedia items require diverse screen layouts. Non-standard templates bring challenges to techers, who either do not have the programming skills or cannot afford the time outside their primary duties to study complex templates. Inflexibility in item creation may cause hesitation in adopting new technologies. In order to support a smooth transition from conventional to multimedia item creation, we introduce a Multimedia Item Generator (MIG) for educators. Portability, reusability, scalability and interoperability are the characteristics of MIG. In this paper, we describe the design and implementation, and present our future plan.